Identification of the PAUD to SD Transition Period Program at the Mobilization Elementary School in Bandung City - Rachmah, Huriah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
Readiness of children to enter elementary school (SD) is always based on their ability to read, write and count (calistung) so that some elementary schools provide calistung ability requirements when entering elementary school. Stages of early age based on The Independent curriculum is 0-8 years old, so early education still lasts until the child steps on the 2nd grade. Therefore the government has launched a transition period program from early childhood to elementary school, which starts in 2023, so that children get their rights acquire the capabilities of the already established foundation. Based on the results of initial observations, the implementation of the transition period in each schools are different so that one reference is needed that can help the school to implement the program. Research it aims to identify the transition period program in 4 (four) schools by using phenomenological methods, so that can produce a transition period program model that can be adapted by other schools.